Investigation of an outbreak of Elizabethkingia meningoseptica on a pediatric intensive care unit - Erinmez, Mehmet; Büyüktas Manay, Ayse; Zer, Yasemin (German Medical Science GMS Publishing House, 2021)
Objective: This paper reports an outbreak on a pediatric intensive care unit with emphasis on investigation of outbreak source, infection control interventions, patient characteristics and comparative antimicrobial susceptibility results.Methods: This was an ambidirectional cohort study conducted in a university hospital 20-bed pediatric intensive care unit. Patient ages ranged from 4 to 11 months, with a median age of 9 months. 83% of the patients had severe underlying conditions. Samples from staff and environmental surfaces were obtained to identify a common source of infection. Antimicrobial susceptibility tests of isolated bacteria were done using the disk diffusion method and the Vitek2 automated system.Results: Environmental surveillance revealed contamination of the water reservoirs of two different mechanical ventilators. antimicrobial susceptibility testing results with two different methods (Vitek2 and disk diffusion) were coherent for most of the investigated antibiotics, but without coherence for ciprofloxacin and levofloxacin. Resistance was found to the relatively new antibiotics ceftaroline and ceftazidime-avibactam.Conclusions: is a significant cause of nosocomial infections, with high mortality especially in children. Investigation of the outbreak source and continuation of intensive infection control precautions are vital to handle outbreaks in PICUs. Using quinolones according to testing results of automated AST systems may lead to inadequate treatment and foster the selection of resistant strains.